The Relationship Between Hopelessness and Suicide Idea in Adolescents - Rahma Annisa; Wita Oktaviana (GLOBAL HEALTH SCIENCE GROUP, 2026)
Suicide is the third leading cause of death in the 15-29 age group. Adolescents with dynamic psychosocial development are highly vulnerable to pressures that can trigger hopelessness and suicidal ideation. Hopelessness is a pessimistic condition about the future, which is related to the emergence of thoughts of ending one's life. This study aims to analyze the relationship between hopelessness and suicidal ideation in adolescents. This quantitative correlational study involved 98 adolescents from SMA Negeri 2 Sukoharjo who were selected through simple random sampling. Data were collected using the Beck Hopelessness Scale (BHS) and Revised–Suicide Ideation Scale (R-SIS) questionnaires, each of which showed high to very high reliability (BHS α = 0.92; R-SIS α = 0.943) and adequate item and construct validity, then analyzed univariately and bivariately using the Spearman correlation test. Results: Most respondents experienced low hopelessness (52%) and low suicidal ideation (78.6%). The Spearman correlation test results showed a correlation coefficient (r) of 0.227 and a p-value of 0.024 (p<0.05). There is a significant but weak positive relationship between hopelessness and suicidal ideation in adolescents. The higher the level of hopelessness, the higher the likelihood of suicidal ideation.